The Role of Good Governance Indicators in Controlling Corruption - Nur, Utami; Mutiarin, Dyah; Jovita, Hazel D.; Palomares, Perla P.; Isolana, Jack B. (Universitas Muhammadiyah Yogyakarta, 2025)
Corruption control is a critical component of effective governance, particularly within local governments in Indonesia. This study examines the relationship between good governance indicators and corruption control within the local government of Yogyakarta City, Indonesia, aiming to identify key governance factors that influence anti-corruption efforts. A quantitative research approach was employed, using descriptive statistical methods to analyze data collected from questionnaires distributed to five local government agencies in Yogyakarta City. A total of 98 respondents were selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to assess the reliability, validity, and regression performance of the good governance indicators. Reliability was measured using Composite Reliability (CR), with values above 0.70 indicating strong reliability, and validity was assessed based on Outer Loading, with values above 0.70 considered valid. Regression analysis indicated that control of corruption, political stability, and voice and accountability significantly influence corruption control, with p-values of 0.010, 0.009, and 0.029, respectively. However, government effectiveness and the rule of law did not show a significant impact on corruption control, with p-values of 0.381 and 0.799. These findings suggest that specific governance factors, such as political stability and accountability, play a critical role in addressing corruption within local governments in Indonesia. The study introduces a novel approach by employing a quantitative SEM-PLS method to examine good governance indicators in Yogyakarta City. The findings suggest that government effectiveness and the rule of law may not have a significant influence on corruption control, challenging common assumptions in governance research.